Phylogenetic Analysis of Thymidin Kinase Gene Koi HerpesVirus (KHV) in Some Freshwater Fish Aquaculture Centers in East Java - Budi Rianto Wahidi (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
Koi Herpesvirus ( KHV ) is a virus that infects goldfish and koi that resulted in mass death and cause economic and social losses. The use of Polymerase Chain Reaction (PCR) technique to detect KHV was done in nila and gurame. Proof that KHV could infect nila and gurame KHV following genetic variation in each definitive host and spreading area have not been done. Based on these problems, this research was conducted to study the genetic variability and genetic relationships between KHV isolates in some freshwater fish as the definitive host koi, komet , koki, nila and gurame that exist in the area of East Java. The results showed that clinically the gills were pale and hemorrage the end of the tail fin. Electrophoresis results showed that all samples from KHV infected koi, koki, komet, nila and gurame were all positive but the sequencing results for tilapia and carp could not be further identified using the BLAST program. Genetically, koi fish, koki and komet isolates were identical to GenBank isolates code KHV-GZ11 and Indo_0K02SS.